Associations between Bystanders and Perpetrators of Online Hate: The Moderating Role of Toxic Online Disinhibition - Wachs, Sebastian; Wright, Michelle F (International journal of environmental research and public health, 2018)
Hatred directed at members of groups due to their origin, race, gender, religion, or sexual orientation is not new, but it has taken on a new dimension in the online world. To date, very little is known about online hate among adolescents. It is also unknown how online disinhibition might influence the association between being bystanders and being perpetrators of online hate. Thus, the present study focused on examining the associations among being bystanders of online hate, being perpetrators of online hate, and the moderating role of toxic online disinhibition in the relationship between being bystanders and perpetrators of online hate. In total, 1480 students aged between 12 and 17 years old were included in this study. Results revealed positive associations between being online hate bystanders and perpetrators, regardless of whether adolescents had or had not been victims of online hate themselves. The results also showed an association between toxic online disinhibition and online hate perpetration. Further, toxic online disinhibition moderated the relationship between being bystanders of online hate and being perpetrators of online hate. Implications for prevention programs and future research are discussed.
Keywords: nenávist; Humans; online disinhibition; studenti; Hate; Female; online hate; perpetrator; lidé; hate speech; on-line systémy; Germany; Německo; Problem Behavior; ženské pohlaví; Communication; Online Systems; Male; online discrimination; problémové chování; Adolescent; komunikace; bystander; Students; mužské pohlaví; cyber aggression; mladiství